Review of Using Instagram Social Media as a Promotional Media on Online Shop Trustworth.id - Endang Dwi Amperawati (Enrichment : Journal of Management, 2022)
In general social media is a media that is used as a means of association online on the Internet. Instagram is one application that is loved. The media used to share photos and videos and can share on other social networking services. In this regard, the author takes the title Review of the Use of social Instagram Media as a Media Promotion at the trustworth.id. The author uses descriptive qualitative analysis research methods, with data collection methods in the form of observation, interviews, and documentation. The results obtained are social media use Instagram as a media campaign on the online shop trustworth.id like features instastory, feature feed Instagram, features the caption, as well as the endorsement and giveaway, 3 of the 4 factors that determine trustworth.id using social media Instagram as a promotional media are cognitive factors, affective and social integration, the use of social media Instagram as a promotional media has been effective because the cost of promotion through social media Instagram is relatively cheap, makes it easy for consumers to access Instagram, easy to use, easy to do promotions and does not need to come directly to the store but the constraints encountered in the promotion such as consumers who are impatient, doubtful and ask lots of questions by giving understanding and explanation that to reply to the chat from the lowest order and provide testimonial results.